Deposition of a TiC/Ti coating with a strong substrate adhesion using a high-speed plasma jet; Surface and Coatings Technology; Vol. 291 - Sivkov A. A. Aleksandr Anatolyevich; Shanenkov I. I. Ivan Igorevich; Pak A. Ya. Aleksandr Yakovlevich; Gerasimov D. Yu. Dmitry Yurievich; Shanenkova Yu. L. Yuliya Leonidovna (2016, 2016)
Title screen